Acute lymphocytic leukemia with initial manifestation of serous retinal detachment and choroidal thickening: case report and literature review. Issue 3 (March 2021) - Yan, Weiming; Wang, Yunpeng; Zheng, Xiangrong; Chen, Xiaohong; Ye, Qian; Chen, Yanjin; Chen, Meizhu
This report describes a patient who had acute lymphocytic leukemia with exudative retinal detachment (RD), which mimicked Vogt–Koyanagi–Harada disease (VKH). A 61-year-old woman presented with painless loss of vision in the left eye. Fundus examination revealed RD in her left eye. B-scan ultrasonography confirmed localized RD and choroidal thickening. Fundus fluorescein angiography revealed stippled pinpoint hyperfluorescence in the upper macula. One week later, reduced visual acuity was noted in the right eye. B-scan ultrasonography and optical coherence tomography revealed serous RD in both eyes. A provisional diagnosis of VKH was made. However, subsequent hematologic analysis detected an extremely high leukocyte count. Elevated numbers of leukocytes and tumor cells were found in cerebrospinal fluid. Bone marrow biopsy revealed 77% primary atypical blood cells, 89% of which were immature lymphocytes. The patient was subsequently diagnosed with acute lymphocytic leukemia and transferred to the Department of Hematology. However, the patient and her family refused chemotherapy; she eventually died. Our findings suggest that exudative RD, similar to VKH, could be a sign of leukemia. Pinpoint hyperfluorescence leakage is important for differential diagnosis, particularly with respect to VKH.